Pengaruh Model Pembelajaran Active Learning terhadap Pengetahuan dan Sikap Penggunaan Alat Pelindung Diri (APD) dalam Pencegahan Terjadinya Green Tobacco Sickness (GTS) pada Buruh Tani Tembakau di Desa Plalangan Kecamatan Kalisat Kabupaten Jember The Effe - Nilla Sahuleka; Hanny Rasni; Ahmad Rifai (Pustaka Kesehatan, 2017)
Green Tobacco Sickness (GTS) suffered by the tobacco leaf pickers who have direct contact withwet tobacco leaves. The method used to increase the knowledge and attitude of the use of personalprotective equipment in order to prevent the occurrence of green tobacco sickness is a learningmodel of active learning on the tobacco farmers. The research objective was to analyze the effect ofactive learning teaching model to the knowledge and attitude of the use of personal protectiveequipment in the prevention of green tobacco sickness among tobacco farmers in the villagePlalangan Kalisat District of Jember. The study design used pre-experimental approach one grouppretest-posttest design. Total population in the study was 836 tobacco farmers with the total sampleof 30 respondents. Sample was selected by using probability sampling. Research data analysisusing the Wilcoxon test showed differences dn knowledge influences attitudes before and afterintervention with p value = 0,000; CI = 95% of the respondents with the following study model ofactive learning. Research conclusion that there was an influence of active learning teaching modelof knowledge and attitude of the use of personal protective equipment. Community health centersprogram is expected to enable the existing occupational health unit, to undergo its role in providinghealth promotion and prevention of work accidents as an occupational health unit.Keywords: active learning model, knowledge and attitude of the use of PPE, Green tobaccosickness